Coherence imaging for ion temperature and flow measurements in a low-temperature helicon plasma source. (25th January 2016) - Lester, R; Zhai, Y; Corr, C; Howard, J
Abstract: This paper describes a coherence imaging system designed for spectroscopic Doppler measurements of ion light in a low-temperature ( T e   <  10 eV) helicon-produced argon plasma. Observation of the very small Doppler broadening of the Ar II 488 nm emission line requires very high spectral resolution, or equivalently, very large interferometric optical path delay (comparable with the coherence length of the emission line). For these polarization interferometers, this can only be achieved using large thicknesses (100 mm) of birefringent crystal. This poses special design challenges including the application of field-widening techniques and the development of passive thermal stabilization of the optical phase offset. We discuss the measurement principles and the optical design of these systems and present measurements of the line-integrated emissivity, and ion flow and ion temperatures along with tomographic reconstructions of the local values, for a cylindrical low temperature helicon discharge in a linear magnetized device with downstream magnetic mirror. Key results reveal a hollow edge-peaked temperature profile (central temperature  ̃0.1 eV) and sheared rigid-body rotational flows and axial flows which are comparable with the ion thermal speed. The emission line brightness, ion temperature and azimuthal ion flows are all found to increase with increased mirror magnetic field strength.